Nutrient Rich Palatable Food Products – Answer to Food Acceptability and Improved Nutrition in CKD Patients - Bhavana Shailendranath; C. Usha Devi; Renuka Satish; Prashant G. Kedlaya (Issues and Developments in Medicine and Medical Research Vol. 7, 2022)
Chronic Kidney Disease (CKD) patients have very poor appetite and added to this they are on polypharmacy, many of which causes nausea and gastroparesis. Majority of patients have diabetes mellitus and hypertension hence cannot consume much salt and sugar. Hence there is poor appeal for food palatability. To improve their intake of nutritious foods it becomes mandatory to venture on good palatable foods with appropriate nutrients bearing in mind renal dietary regimen. This includes limiting potassium, salt content and fluid in foods. Our effort of present publication is on this line. Five renal food products were prepared and each was subjected to sensory evaluation among thirty subjects of patient group and controls. There was satisfactory acceptance for all the renal foods showing its palatability.